Harnessing indigenous knowledge on ethnomedicinal plants for malaria treatment in South Manokwari, West Papua, Indonesia - RIMA HERLINA SETIAWATI SIBURIAN; RUSDI ANGRIANTO; YAFET SYUFI; BAMBANG NUGROHO; MARYROSE EASTER TAPILATU; JULIA ROSEMARY TAPILATU (Society for Indonesian Biodiversity, 2025)
Abstract. Siburian RHS, Angrianto R, Syufi Y, Nugroho B, Tapilatu ME, Tapilatu JR. 2025. Harnessing indigenous knowledge on ethnomedicinal plants for malaria treatment in South Manokwari, West Papua, Indonesia. Biodiversitas 26: 3408-3422. Malaria, an endemic disease in Papua, Indonesia, including South Manokwari, West Papua, has become a critical public health issue due to increasing drug resistance resulting from the routine use of antimalarial drugs. This issue highlights the importance of exploring medicinal plants as potential sources of new antimalarial agents. This study aims to document ethnomedicinal plants used for malaria treatment in South Manokwari District, using ethnobotanical and anthropological approaches. Data were collected through interviews with 88 participants aged 18 years and older, consisting of 34% male and 66% female. A total of 57 species of medicinal plants from 25 families were identified for malaria treatment. Relative Frequency of Citation (RFC) values ranged from 3.41 to 31.82, and the Fabaceae family was the most represented, with 8 species used for medicine, followed by Meliaceae and Myrtaceae families, each with 5 species. Preference ranking identified Andrographis paniculata (RFC: 31.82) as the top choice, followed by Carica papaya (RFC: 29.55) and Alstonia scholaris (RFC: 23.86). Plant parts used included leaves, stems, bark, roots, fruits, flowers, and seeds. Methods of application varied and included drinking, massaging, bathing, inhalation, and evaporation, with drinking being the most common method. The bioactive compounds in these plants are expected to contribute valuable references for the development of new antimalarial agents. Therefore, the conservation and future availability of their natural compounds should be prioritized.